Correlates of sedentary behaviour among Bhutanese adolescents: Findings from the 2016 Global School-based health survey. (December 2020) - Dendup, Tashi; Putra, I Gusti Ngurah Edi; Dorji, Tandin; Tobgay, Tashi; Dorji, Gampo; Phuntsho, Sonam; Tshering, Pandup
Highlights: Higher grade, day student, and unhealthy food intake were related to higher odds of sedentariness. Loneliness, suicidal thoughts, substance use, and physical activity were associated with higher odds. Short sleep was associated with lower odds, while long sleep was associated with greater odds. The associations differed by gender for some factors of sedentary behaviour. Abstract: Background: Sedentary behaviour is shown to be associated with cardiometabolic health including obesity, and mental health. This study examined the factors associated with sedentary behaviour among Bhutanese adolescents. Methods: The nationally-representative dataset of the Bhutan Global School-based Health Survey conducted in 2016 was analysed in this study. Multiple logistic regression using the backward elimination approach was performed to identify the factors associated with sedentariness. The analysis accounted for the complex survey design of the national survey. Results: The weighted prevalence of sedentary behaviour among Bhutanese adolescents was 29.12%. The multivariable analysis showed that higher grades, being a day student, consumption of soft drinks and fast foods, substance use, feeling lonely and suicidal behaviour were associated with higher odds of sedentary behaviour. Short duration of sleep was associated with reduced odds of sedentariness, whereas longer duration with increased odds. In the girls' sample, higher grade, student type, fast food intake, physical activity, longer sleep duration, substance use, and suicidal thought were the factors predicting sedentariness. Among boys, higher grade, soft drink and fast food consumption, physical activity, short sleep duration, smoking and drug use, and loneliness were the significant factors. Conclusions: The results suggest plausible gender differences in the factors influencing sedentariness among adolescents of Bhutan. Gender-specific policies such as those aimed to reduce substance abuse, increase access to mental health services, and promote healthy lifestyles and behaviours are needed to reduce the adverse impacts of sedentary behaviour. Interventions targeting students in higher grades and day students may yield larger gains.